OPTIMASI DISTRIBUSI MULTIPLE PRODUCTS PADA MULTIPLE BUYERS MENGGUNAKAN MULTI-VEHICLE PADA CAPACITATED VEHICLE ROUTING PROBLEM - , ZITA IGA PRAMUDITHA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Distribution system is one of the most important activities within company for reaching its customers. The location differences of the customers can be solved by applying efficient distribution system. Distribution system which is not doing properly will also cause raising overall company expenses. Thus, having optimized distribution system is a necessity for every company. A mathematical model of Vehicle Routing Problem is built in this research. The system that has been observed in this research is PT. Kimia Farma Trading and Distribution Yogyakarta. The model characteristics are single distribution center, multiple products, multiple buyers. Distribution center delivers the multiple produtcs to 56 customers a day. Integer linear programming is used to built the model and the decision variable is in the form of binary integer. The objective function of the model is to minimize distribution cost at each period. The mathematical model is solved using LINGO. The result of the model is compared to the existing system to determine the system having less cost in distribution system. Based on the optimizing process, the vehicle route can be evaluated. The motorcycle customer which are located in a car route are delivered by car. By doing this, the delivery cost decreases about 22,97% compared to the exiting condition. The distribution cost also decreses about 1,67% and time saving 233,88 minutes compared to the my previous research. In this research, there are four distribution scenarios that provide the alternatives to do distribution which may be the consideration for the distribution center.